Assessing the Impact of the Independent Learning Curriculum: A Case Study in Elementary Schools - Rizka Safitri; Mohamad Agung Rokhimawan (STAI Hubbulwathan Duri, 2024)
This study evaluates the implementation of the independent learning curriculum in elementary schools using the Context, Input, Process, Product (CIPP) evaluation model. Addressing this curriculum's effectiveness is essential for enhancing educational quality, resources, teaching strategies, and student learning outcomes. A mixed-methods approach was adopted, involving qualitative interviews and quantitative questionnaires to collect data from a principal, a vice principal for curriculum, and 15 teachers. This dual approach enabled an in-depth examination of curriculum implementation factors. Analysis reveals that the independent learning curriculum is implemented effectively and efficiently.